2020
DOI: 10.1111/bph.15028
|View full text |Cite
|
Sign up to set email alerts
|

GPCRs in pancreatic adenocarcinoma: Contributors to tumour biology and novel therapeutic targets

Abstract: Pancreatic cancer has one of the highest mortality rates (5‐year survival ~9%) among cancers. Pancreatic adenocarcinoma (PAAD) is the most common (>80%) and the most lethal type of pancreatic cancer. A need exists for new approaches to treat pancreatic adenocarcinoma. GPCRs, the largest family of cell‐surface receptors and drug targets, account for ~35% of approved drugs. Recent studies have revealed roles for GPCRs in PAAD cells and cells in the tumour micro‐environment. This review assesses current informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 127 publications
0
18
0
Order By: Relevance
“…Since GPCRs can signal through the G12 family of small G proteins (Kurose, 2003), many studies have evaluated the contribution of Gα12 and Gα13 to physiologic and pathologic processes (Sriram et al, 2020;Syrovatkina and Huang, 2019;Tutunea-Fatan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since GPCRs can signal through the G12 family of small G proteins (Kurose, 2003), many studies have evaluated the contribution of Gα12 and Gα13 to physiologic and pathologic processes (Sriram et al, 2020;Syrovatkina and Huang, 2019;Tutunea-Fatan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in understanding the role of effectors downstream of GPCRs and determining whether these effectors could be potential therapeutic targets (Hauser et al, 2017). Since GPCRs can signal through the G12 family of small G proteins (Kurose, 2003), many studies have evaluated the contribution of Gα12 and Gα13 to physiologic and pathologic processes (Sriram et al, 2020; Syrovatkina and Huang, 2019; Tutunea-Fatan et al, 2020). These studies, which have been primarily performed in epithelial cancer cell lines, showed that Gα13 functions as a tumor promoter (Chow et al, 2016; Kelly et al, 2007; Kelly et al, 2006; Kozasa et al, 2011; Rasheed et al, 2018; Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is extremely beneficial in the study of GPCRs located at the plasma membrane as the receptors are typically not only at the cell membrane, but also at intracellular sites such as endosomes, endoplasmic reticulum, and the Golgi complex [38] and TIRF imaging minimizes their intracellular visualisation. Next, we aimed to demonstrate the applicability of qPAINT analysis to quantitatively P2Y 2 receptors were labelled with a primary antibody which we validated using the immortalised human pancreatic stellate cell line PS-1 as it expresses traces amounts of the protein of interest (see Figure S2 for negative control results) [19,39]. For DNA-PAINT imaging, the anti-P2Y 2 receptor antibody was chemically coupled to an optimised docking strand sequence design to increase imaging speed.…”
Section: Super-resolution Imaging Of P2y 2 Receptors In Aspc-1 Cells Using Dna-paintmentioning
confidence: 99%
“…Functional aspects of GPCR have been established in cancers, including pancreatic cancer, both in the cells of cancer and tumor microenvironment. A wide variety of GPCRs are expressed by pancreatic adenocarcinoma tumor cells [ 145 ]. As the GPCRs are the largest drug target family, about 34% of all drugs approved by the Food and Drug Administration (FDA) targeted 108 members of GPCR [ 146 ].…”
Section: Role Of G Protein-coupled Receptor In Pancreatic Cancermentioning
confidence: 99%